Magnetic Properties of Ultrathin Magnetite Films Grown by Molecular Beam Epitaxy - SHVETS, IGOR; ARORA, SUNIL; WU, HAN-CHUN (IEEE-INSTITUTE OF ELECTRICAL AND ELECTRONIC ENGINEERS INC, 2008)
Magnetic properties as a function of film thickness (2-55 nm) for magnetite (Fe3O4) thin films grown on MgO (100) substrates show that the small thickness films (les 5 nm) are ferromagnetic and possess magnetization values which are much greater than that of bulk Fe3O4 . The inverse thickness dependence of the magnetization points to an interface related mechanism. Whereas, our detailed spin polarized density functional theoretical calculations suggests that there is only a marginal enhancement in the local spin moments of Fe-atom in the vicinity of the Fe3O4-MgO interface and it turns out that the noncompensation of spin moments between the two magnetic sublattices of spinel Fe3O4 is a major factor contributing to the enhancement of magnetization.
IEEE Transactions on Magnetics
International Magnetics Conference (Intermag)
PUBLISHED
Madrid, Spain
Keywords: Atomic, molecular and chemical physics; thin films